Effect of immersion cryotherapy on blood lactate clearance after exercise - Bruno Manfredini Baroni; Rafael Abeche Generosi; Douglas Grosselli; Sinara Censi; Flavia Bertolla; Ernesto Cesar Pinto Leal Junior (Universidade Federal de Santa Catarina, 2010)
The objective of this study was to analyze the effect of immersion cryotherapy on blood lactate removal, an important physiological parameter related to muscle fatigue, after high-intensity exercise. Fifteen soccer athletes (15 to 17 years) were randomized into an immer-sion group (IG, n=7) and a control group (CG, n=8). The athletes were subjected to a muscle fatigue inducer protocol (PIFM) on a cycle ergometer. Next, GI athletes underwent immersion cryotherapy for 10 minutes, with the lower limbs being immersed at 5±1º C, whereas CG athletes rested for 10 minutes. Blood samples were collected for the determination of lactate concentration before the PIFM and 3, 15 and 25 minutes after the end of exercise (post-3, post-15 and post-25, respectively). The PIFM resulted in a significant increase of blood lactate concentration in the athletes, which was similar in two groups. During the recovery period, lactate concentration decreased by 13.6% at post-15 and by 15.3% at post-25 in IG, whereas GC presented a decrease of 14.6% and 28.5% decrease at post-15 and post-25, respectively. Passive recovery resulted in a significant decrease of lactate concentration, whereas the same was not observed for cryotherapy. These results suggest that, for the parameters used in this study, immersion cryotherapy was less effective than rest in the removal of blood lactate after high-intensity exercise.